Effect of retirement on health and work ability among municipal employees. - Tuomi, Kaija; Jarvinen, E; Eskelinen, Leena; Ilmarinen, Juhani; Klockars, Matti (Scandinavian Journal of Work, Environment & Health, 1991)
A questionnaire was sent to 6257 active employees, mean age 50.5 years, in 1981, and again in 1985, when 4255 of the workers were still actively working, 402 had retired because of age, and 468 had retired for medical reasons. After retirement, regardless of reason or previous work content, the prevalence of musculoskeletal diseases changed little among the women but increased markedly among the men retired from mental work. Among the men retired from mental work because of age, the prevalence of cardiovascular diseases increased after retirement. After disability pensioning the prevalence of cardiovascular diseases increased for both the men and the women. The prevalence of poor work ability increased in all the work categories irrespective of the type of retirement. Work ability did not improve after old-age pensioning, but health status was improved among the men and women in some occupational groups. Therefore light, part-time work should not be excluded for retired people.